PREPARATION OF FUTURE VOCATIONAL SCHOOL TEACHERS FOR THE ORGANIZATION OF YOUTH ENTREPRENEURSHIP CONSULTING IN VOCATIONAL (VOCATION-TECHNICAL) EDUCATION INSTITUTIONS (Innovative professional education, 2022)
The educational-professional and educational-scientific programs for the training of higher education seekers in the specialty 015 Vocational education (by specializations) were analyzed in order to find out their possibilities for training future teachers of a vocational school to implement consulting on youth entrepreneurship in institutions of professional (vocational and technical) education. Recommendations for updating the content of educational programs, taking into account the tasks of modern educational legislation regarding the development of career and entrepreneurial competencies of future specialists, have been formulated.
Keywords: professional education, youth entrepreneurship consulting, professional (vocational and technical) education institutions, educational programs